Size Distribution of Massive Porites at Reef Flat in Kondang Merak, Malang, Indonesia - Oktiyas Muzaky Luthfi; Putri Zulaikhah Alviana; Guntur Guntur; Sunardi Sunardi; Alfan Jauhari (Research Journal of Life Science, 2016)
Kondang Merak was lied on south of Java sea that has monitored coral reef inside. Environment condition such as load of terrestrial’s nutrient into the sea, increase of surface water temperature and tourism activities were affected on coral reef health. The massive Porites that common coral found in this location need be monitored gradually to see coral condition over time. The research was conducted on May 2015 in reef flat area of Kondang Merak. The aims of the research were to know distribution of massive Porites and oceanography condition in Kondang Merak. The highest sea surface temperature was 26,46o C in transect number 2 at station 1 (eastern part). Salinity of sea water was in normal range between 34, 42o/oo to 35,75o/oo, dissolved oxygen was on range 6 mg/l sampai 9,1 mg/l and pH was 7,23 sampai 8,68 respectively. Two species on massive Porites they were Porites lobata dan P. lutea. In station 1 the average diameter of P. lobata was 228.57 cm and P. lutea 63.89 cm, in while P. lobata in station 2 was 260.57 cm and P. lutea 153.56 cm.